Rola innowacyjności w proeksportowej restrukturyzacji polskiego przemysłu - Talar, Sylwia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Innovation is considered as a key source of competitiveness advantage and the pre-condition of persistent economic development in the contemporary world economy. From this point of view, the growth of innovation should be the main determinant of export development. But the research of Polish manufacturing in the period of 1994-2006 shows that export intensity growth was not in relation to innovation growth. The same situation is as regards the level of Polish manufacturing export propensity. There was not relation to innovation measured by the scale of enterprises expenditure on all types of innovation activity as well as the output of this activity (sales due to technologically new and improved products introduced into the market during three last years as a share of total sold production). Taking into account that industrial enterprises innovation did not determine the pro-export restructuring of Polish manufacturing, it can be expected that demand and cost factors were the reason for this process in Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 675-685